Preparation method of composite hydrogel loaded with mesoporous silicon nanomaterial
By loading the mesoporous silicon nanomaterials on chitosan and β-glycerol sodium phosphate hydrogels, the problem of poor drug loading and release control in traditional hydrogels is solved, and efficient drug loading and controlled release are achieved, improving the therapeutic effect and providing antibacterial functions.
Patent Information
- Application Number
- CN202411799531.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-28
AI Technical Summary
Traditional hydrogels face problems in biomedical applications with limited drug load capacity, poor release control and lack of specific biological functions.
By loading the mesoporous silicon nanomaterial on a hydrogel synthesized with chitosan and β-glycerol sodium phosphate as the main raw materials, the high specific surface area and good biocompatibility of the mesoporous silicon nanomaterials are used to enhance the drug loading and controlled release capabilities of the hydrogel.
The efficient drug load and controlled release of hydrogels are achieved, the therapeutic effect is improved, and the antibacterial mechanism is provided through the photothermal conversion ability, reducing the risk of wound infection.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a composite hydrogel loaded with mesoporous silicon nanomaterials, and specifically relates to the preparation of a mesoporous silicon nanomaterial and the preparation of a hydrogel loaded with the mesoporous silicon nanomaterial and synthesized with chitosan and sodium β-glycerophosphate as main raw materials, and the microscopic morphology and biocompatibility of the material are studied. The present invention belongs to the field of nano-biomedical materials. Background Art
[0002] In today's biomedical materials field, hydrogels have attracted much attention due to their unique hydrophilicity, biocompatibility, and tunable mechanical properties. Especially in hemostasis and wound repair, hydrogels have shown great application potential. However, traditional hydrogels still face some challenges in practical applications, such as limited drug loading capacity, poor release control, and lack of specific biological functions. In order to overcome these problems, researchers began to explore the combination of nanotechnology and hydrogels to develop new biomedical materials with higher performance.
[0003] Among them, mesoporous silicon nanomaterials are ideal for improving the performance of hydrogels due to their uniform mesoporous structure, high specific surface area, good biocompatibility and biodegradability. The introduction of mesoporous silicon nanomaterials can not only enhance the drug loading capacity of hydrogels, but also achieve sustained and controlled release of drugs, thereby improving the therapeutic effect. In addition, the photothermal conversion ability of mesoporous silicon nanomaterials also provides a new antibacterial mechanism for hydrogels, which helps reduce the risk of wound infection.
[0004] In terms of hemostasis and wound repair, composite hydrogels loaded with mesoporous silica nanomaterials have shown significant advantages. First, its high water absorption rate and excellent mechanical properties enable it to quickly absorb blood on the wound surface and form stable blood clots, thereby effectively controlling bleeding. Secondly, the mesoporous silica nanomaterials in the composite hydrogel can promote angiogenesis and cell proliferation, accelerating the wound healing process. In addition, by adjusting the structure and composition of mesoporous silica nanomaterials, the drug release rate can also be precisely controlled to meet the needs of different treatment stages.
[0005] Although composite hydrogels loaded with mesoporous silica nanomaterials have shown great potential in hemostasis and wound repair, their practical application still faces some challenges. For example, how to ensure the stability and biosafety of hydrogels in the body, how to optimize the drug release system to improve the therapeutic effect, and how to achieve large-scale production all require further research and solutions. Therefore, future research needs to continue to explore the interaction mechanism between mesoporous silica nanomaterials and hydrogels, optimize the preparation process, and improve the performance and stability of the product to promote its widespread application in the biomedical field. Summary of the invention
[0006] The present invention aims to provide a method for preparing a composite hydrogel loaded with mesoporous silicon nanomaterials.
[0007] Another object of the present invention is to provide a product obtained by the above method.
[0008] Another object of the present invention is to provide applications of the product.
[0009] The object of the present invention is achieved by the following scheme: A method for preparing a composite hydrogel loaded with mesoporous silicon nanomaterials, comprising the preparation of a mesoporous silicon nanomaterial and loading it on a hydrogel synthesized with chitosan and sodium β-glycerophosphate as main raw materials, comprising the following steps: 1) Preparation of mesoporous silicon nanomaterials (1) After placing a stirring bar in a beaker, add 45 ml of deionized water, 8 ml of anhydrous ethanol, 5 ml of a 10 wt% sodium hydroxide aqueous solution, and 1.8 g of cetyltrimethylammonium bromide (CTAB) in sequence, stir well, and let stand overnight to obtain a mixed solution; (2) Add 4.2 g of tetraethyl orthosilicate (TEOS) to the mixed solution, stir thoroughly and let stand overnight, then divide the sample into centrifuge tubes and centrifuge at 5000 r for 5 min, aspirate the supernatant and add deionized water, ultrasonicate at 50 Hz and room temperature for 5 min, let stand, wash away the supernatant and add deionized water for washing, repeat twice, then further wash three times with anhydrous ethanol to obtain the sample; (3) adding ammonium nitrate ethanol solution to the sample, further centrifuging to remove the supernatant, and repeating three times to remove CTAB on the sample surface; (4) drying the sample in step (3) in a drying oven at 70°C overnight, and then calcining the sample in a muffle furnace at 400°C for 4 hours. Finally, the sample was taken out and ground to obtain a mesoporous silicon nanomaterial. 2) Preparation of composite hydrogel (1) exposing chitosan powder to ultraviolet light overnight for sterilization and dispensing the chitosan powder in deionized water with a solid-liquid ratio of 1 g:25 mL, adding hydrochloric acid with an equal volume to the deionized water and a final concentration of 0.1 M under stirring, keeping the solution at room temperature overnight to ensure that the chitosan is completely dissolved, and storing at 4°C to obtain a chitosan solution; (2) β-glycerophosphate disodium salt hydrate (β-GP) was dissolved in deionized water and sterilized using a 0.22 μm filter, and then the mesoporous silica nanomaterials were added and shaken to mix; (3) The gelling agent synthesized in the previous step was added to the prepared chitosan solution while stirring to obtain a uniformly mixed system, which was then immersed in a 37°C water bath to prepare a composite hydrogel.
[0010] Furthermore, the mesoporous silicon nanomaterial is prepared according to the following steps: (1) Place a stirring bar in a beaker, then add 45 ml of deionized water, 8 ml of anhydrous ethanol, 5 ml of a 10 wt% sodium hydroxide solution, and 1.8 g of cetyltrimethylammonium bromide (CTAB) in sequence, stir well to mix, and let stand overnight; (2) Add 4.2g of tetraethyl orthosilicate (TEOS) to the mixture, stir thoroughly and let stand overnight. Then divide the sample into centrifuge tubes and centrifuge at 5000r for 5min. After absorbing the supernatant, add deionized water, ultrasonicate at 50HZ and room temperature for 5min, let stand, wash away the supernatant and add deionized water for washing, repeat twice, and then further wash three times with anhydrous ethanol; (3) adding ammonium nitrate ethanol solution to the cleaned sample, further centrifuging to remove the supernatant, and repeating three times to remove CTAB on the sample surface; (4) The sample was placed in a drying oven at 70°C for overnight drying, and then placed in a muffle furnace for constant temperature calcination at 400°C for 4 hours. Finally, the sample was taken out and ground to obtain mesoporous silicon nanomaterials.
[0011] Preferably, the sample is calcined for 3-6 hours at a temperature of 300-500°C.
[0012] Furthermore, the composite hydrogel is prepared according to the following steps: (1) Chitosan powder was exposed to ultraviolet light overnight for sterilization and 1 g was dispensed in 25 ml of deionized water, and then 25 ml of 0.2 M hydrochloric acid solution (final hydrochloric acid concentration was 0.1 M) was added under stirring. The solution was kept at room temperature overnight to ensure that the chitosan was completely dissolved, and then stored at 4 °C to obtain a chitosan solution; (2) β-GP was dissolved in deionized water and sterilized using a 0.22 μm filter, and then the mesoporous silica nanomaterials were added and shaken to mix; (3) The gelling agent synthesized in step (2) is added to the prepared chitosan solution while stirring to obtain a uniformly mixed system, which is then immersed in a 37° C. water bath to prepare a composite hydrogel loaded with mesoporous silica nanomaterials.
[0013] The present invention also provides a composite hydrogel product loaded with mesoporous silicon nanomaterials obtained by the method.
[0014] The invention prepares a mesoporous silicon nano material and loads the mesoporous silicon nano material in a thermosensitive hydrogel synthesized with chitosan and sodium beta-glycerophosphate as main raw materials.
[0015] The present invention explores the biocompatibility of the above product by detecting the hemolysis rate of the product, and has the characteristics of a hemolysis rate of less than 5% and good biocompatibility.
[0016] The hemolysis test method is as follows: (1) Collect fresh blood from healthy SD rats, put it into anticoagulant tubes, and then centrifuge it at 8000r for 5min. Discard the supernatant and add it to PBS for centrifugation again. Repeat the washing three times and dilute it with appropriate amount of PBS. Seal it and store it at 4℃. (2) Take 5 ml of the composite hydrogel and sterilize it with ultraviolet light overnight, then put it into 50 ml centrifuge tubes, add 45 ml of PBS, seal and soak for 48 hours; (3) Take 500ul of the extracted PBS and diluted blood respectively into a 1.5ml centrifuge tube, incubate in a 37℃ incubator for 2 hours, then centrifuge (8000r, 5min), and finally take the supernatant into a 96-well plate. Use enzyme marker to measure the absorbance at 545nm, and calculate the hemolysis percentage according to the relevant formula.
[0017] The incubation time of the extract should be 2-4h.
[0018] Hemolysis experiments should use fresh blood from healthy 6-8 week old SD rats.
[0019] The present invention prepares a mesoporous silicon nanomaterial and loads it in a thermosensitive hydrogel synthesized with chitosan and sodium β-glycerophosphate as main raw materials, and explores its biocompatibility by detecting the hemolysis rate.
[0020] In the present invention, a mesoporous silicon nanomaterial with uniform size is prepared and loaded on a chitosan-based hydrogel to form a composite hydrogel, and then the microscopic morphology and biocompatibility of the material are studied.
[0021] The advantages of the present invention are: (1) The thermosensitive hydrogel used in the present invention is synthesized using chitosan and sodium β-glycerophosphate as main raw materials. The raw materials used have high biological safety, and some of them are already commercial products.
[0022] (2) The synthesis cost of the mesoporous silicon nanomaterial prepared by the present invention is reduced, meeting the requirements of industrialization.
[0023] (3) The preparation method of the present invention has simple process and strong operability, which can further meet the needs of production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope image of the mesoporous silicon prepared in Example 1; Figure 2 is a transmission electron microscope image of the mesoporous silicon prepared in Example 1; Figure 3The scanning electron microscope images of the hydrogels prepared in Examples 1 and 2; Figure 4 This is a scanning electron microscope image of the mesoporous silica-loaded hydrogel prepared in Example 1; Figure 5 These are the results and analysis images obtained from the hemolysis experiments performed in Examples 1, 2, 3, and 4. DETAILED DESCRIPTION
[0025] The technical scheme of the present invention is further described below through specific examples. The following examples are further explanations of the present invention, but do not limit the scope of the present invention.
[0026] Example 1 A composite hydrogel loaded with mesoporous silicon nanomaterials is prepared according to the following steps: 1) Preparation of mesoporous silicon nanomaterials (1) After placing a stirring bar in a beaker, add 45 ml of deionized water, 8 ml of anhydrous ethanol, 5 ml of a 10 wt% sodium hydroxide aqueous solution, and 1.8 g of cetyltrimethylammonium bromide (CTAB) in sequence, stir well, and let stand overnight to obtain a mixed solution; (2) Add 4.2 g of tetraethyl orthosilicate (TEOS) to the mixed solution, stir thoroughly and let stand overnight, then divide the sample into centrifuge tubes and centrifuge at 5000 r for 5 min, aspirate the supernatant and add deionized water, ultrasonicate at 50 Hz and room temperature for 5 min, let stand, wash away the supernatant and add deionized water for washing, repeat twice, then further wash three times with anhydrous ethanol to obtain the sample; (3) Adding an ethanol solution of ammonium nitrate to the sample, further centrifuging to remove the supernatant, repeating three times to remove the CTAB on the surface of the sample, and obtaining a sample; after the sample is placed in a drying oven at 70°C for overnight, it is placed in a muffle furnace and calcined at 400°C for 4 hours, and finally the sample is taken out and ground to obtain a mesoporous silicon nanomaterial.
[0027] Figure 1 This is a scanning electron microscope image of the prepared mesoporous silicon nanomaterial. It can be seen that the prepared mesoporous silicon has uniform size and obvious pore structure on the surface, and is expected to become a relatively excellent biomaterial.
[0028] Figure 2 This is a transmission electron microscope image of the prepared mesoporous silicon nanomaterial. The image further verifies that the size of the mesoporous silicon is uniform and that the surface has pores.
[0029] 2) Preparation of composite hydrogel (1) exposing chitosan powder to ultraviolet light overnight for sterilization and dispensing 0.1 g of chitosan powder in 2.5 ml of deionized water, adding 2.5 ml of 0.2 M hydrochloric acid solution under stirring to a final concentration of 0.1 M, keeping the solution at room temperature overnight to ensure that the chitosan is completely dissolved, and storing at 4°C to obtain a chitosan solution; (2) Dissolve 0.25 g of β-glycerophosphate disodium salt hydrate (β-GP) in 0.5 ml of deionized water and sterilize using a 0.22 μm filter, then add the mesoporous silica nanomaterials and shake to mix; (3) The gelling agent synthesized in step (2) is added to the prepared chitosan solution while stirring to obtain a uniformly mixed system, which is then immersed in a 37° C. water bath to prepare a chitosan-based composite hydrogel.
[0030] like Figure 3 As shown, the scanning electron microscope image of the prepared chitosan-based hydrogel shows that the hydrogel has a distinct pore structure and is expected to be loaded with drugs and applied to wound dressings.
[0031] Figure 4 This is a scanning electron microscope image of the prepared composite hydrogel. It can be seen that the mesoporous silica material is successfully attached to the chitosan-based hydrogel without destroying the structure of the hydrogel.
[0032] 4. Hemolysis Test (1) Collect fresh blood from healthy SD rats, put it into anticoagulant tubes, and then centrifuge at 8000r for 5min. Discard the supernatant and add it to PBS for centrifugation again. Repeat the washing three times and dilute it with appropriate amount of PBS. Seal it and store it at 4°C. (2) Take 5 ml of the composite hydrogel and sterilize it with ultraviolet light overnight, then put it into a 50 ml centrifuge tube, add 45 ml of PBS, seal and soak for 48 hours; (3) Take 500ul of the extracted PBS and diluted blood respectively in a 1.5ml centrifuge tube, incubate in a 37℃ incubator for 2 hours, then centrifuge (8000r, 5min), and finally take the supernatant into a 96-well plate. Use an enzyme marker to measure the absorbance at 545nm, and calculate the hemolysis percentage according to the relevant formula.
[0033] The results of the hemolysis experiment are shown in Figure 5 shown.
[0034] Example 2 A chitosan-based hydrogel is prepared according to the following steps: (1) Expose chitosan powder to ultraviolet light overnight for sterilization and take 0.1 g of it and dispense it in 2.5 ml of deionized water. Then, add 2.5 ml of 0.2 M hydrochloric acid solution (final hydrochloric acid concentration is 0.1 M) under stirring. Keep the solution at room temperature overnight to ensure that the chitosan is completely dissolved, and then store it at 4 °C. (2) Dissolve 0.25 g of β-GP in 0.5 ml of deionized water and sterilize it using a 0.22 μm filter. Add the gelling agent to the prepared chitosan solution while stirring to obtain a uniformly mixed system, and then immerse it in a 37°C water bath to obtain a chitosan-based hydrogel.
[0035] like Figure 3 As shown, the scanning electron microscope image of the prepared chitosan-based hydrogel shows that the hydrogel has a distinct pore structure and is expected to be loaded with drugs and applied to wound dressings.
[0036] The obtained chitosan-based hydrogel was subjected to a hemolysis experiment according to the following steps: (1) Collect fresh blood from healthy SD rats, put it into an anticoagulant tube, and then centrifuge it at 8000r for 5min. Discard the supernatant and add it to PBS for centrifugation again. Repeat the washing three times and add an appropriate amount of PBS for dilution. Seal it and store it at 4°C to obtain the extracted PBS. (2) Take 5 ml of chitosan-based hydrogel and sterilize it with ultraviolet light overnight, then put it into 50 ml centrifuge tubes, add 45 ml of PBS, seal and soak for 48 hours to obtain diluted blood; (3) Take 500ul of the extracted PBS and diluted blood respectively in a 1.5ml centrifuge tube, incubate in a 37℃ incubator for 2 hours, then centrifuge (8000r, 5min), and finally take the supernatant into a 96-well plate. Use an enzyme marker to measure the absorbance at 545nm, and calculate the hemolysis percentage according to the relevant formula.
[0037] The results of the hemolysis experiment are shown in Figure 5 shown.
[0038] Example 3 Hemolysis test: (1) Collect fresh blood from healthy SD rats, put it into an anticoagulant tube, and then centrifuge it at 8000r for 5min. Discard the supernatant and add it to PBS for centrifugation again. Repeat the washing three times and add an appropriate amount of PBS for dilution. Seal it and store it at 4°C to obtain diluted blood. (2) Take 5 ml of deionized water and sterilize it with ultraviolet light overnight, then put it into 50 ml centrifuge tubes, add 45 ml of PBS, seal and soak for 48 hours to obtain the extracted PBS; Step 3: Take 500ul of the extracted PBS and diluted blood in a 1.5ml centrifuge tube, incubate in a 37℃ incubator for 2 hours, then centrifuge (8000r, 5min), and finally take the supernatant in a 96-well plate, measure the absorbance at 545nm with an enzyme marker, and calculate the hemolysis percentage according to the relevant formula.
[0039] Example 4 Hemolysis test: Step 1: Collect fresh blood from healthy SD rats, put it into an anticoagulant tube, and then centrifuge it at 8000r for 5min. Discard the supernatant and add it to PBS for centrifugation again. Repeat the washing three times and add an appropriate amount of PBS for dilution. After sealing, store it at 4°C to obtain diluted blood. (2) Take 5 ml of PBS solution and sterilize it with ultraviolet light overnight, then put it into 50 ml centrifuge tubes, add 45 ml of PBS, seal and soak for 48 hours to obtain the extracted PBS; (3) Take 500ul of the extracted PBS and diluted blood respectively in a 1.5ml centrifuge tube, incubate in a 37℃ incubator for 2 hours, then centrifuge (8000r, 5min), and finally take the supernatant into a 96-well plate. Use an enzyme marker to measure the absorbance at 545nm, and calculate the hemolysis percentage according to the relevant formula.
[0040] The results of the hemolysis experiment are shown in Figure 5 shown.
[0041] Figure 5 The results of the hemolysis experiments conducted in Examples 1, 2, 3, and 4 show that the hemolysis rate of the composite hydrogel prepared in Experimental Example 1 is less than 5%. According to the American Society for Testing and Materials (ASTM) standard, materials with a hemolysis rate of less than 5% can be used in biomedical applications. This shows that the prepared composite hydrogel has good blood compatibility and can be reasonably used in burn dressings.
Claims
1. A method for preparing a composite hydrogel loaded with mesoporous silicon nanomaterials, characterized in that: The method comprises the preparation of a mesoporous silicon nanomaterial and loading the mesoporous silicon nanomaterial on a hydrogel synthesized with chitosan and sodium β-glycerophosphate as main raw materials, and comprises the following steps: 1) Preparation of mesoporous silicon nanomaterials (1) After placing a stirring bar in a beaker, add 45 ml of deionized water, 8 ml of anhydrous ethanol, 5 ml of a 10 wt% sodium hydroxide aqueous solution, and 1.8 g of cetyltrimethylammonium bromide (CTAB) in sequence, stir well, and let stand overnight to obtain a mixed solution; (2) Add 4.2 g of tetraethyl orthosilicate (TEOS) to the mixed solution, stir thoroughly and let stand overnight, then divide the sample into centrifuge tubes and centrifuge at 5000 r for 5 min, aspirate the supernatant and add deionized water, ultrasonicate at 50 Hz and room temperature for 5 min, let stand, wash away the supernatant and add deionized water for washing, repeat twice, then further wash three times with anhydrous ethanol to obtain the sample; (3) adding ammonium nitrate ethanol solution to the sample, further centrifuging to remove the supernatant, and repeating three times to remove CTAB on the sample surface; (4) drying the sample in step (3) in a drying oven at 70°C overnight, and then calcining the sample in a muffle furnace at 300-500°C for 3-6 hours. Finally, the sample was taken out and ground to obtain a mesoporous silicon nanomaterial. 2) Preparation of composite hydrogel (1) exposing chitosan powder to ultraviolet light overnight for sterilization and dispensing the chitosan powder in deionized water with a solid-liquid ratio of 1 g:25 mL, adding hydrochloric acid with an equal volume to the deionized water and a final concentration of 0.1 M under stirring, keeping the solution at room temperature overnight to ensure that the chitosan is completely dissolved, and storing at 4°C to obtain a chitosan solution; (2) dissolving β-glycerophosphate disodium salt hydrate (β-GP) in deionized water and sterilizing it using a 0.22 μm filter, then adding mesoporous silica nanomaterials and shaking to mix; (3) The gelling agent synthesized in the previous step was added to the prepared chitosan solution while stirring to obtain a uniformly mixed system, which was then immersed in a 37°C water bath to prepare a composite hydrogel.
2. The method for preparing the composite hydrogel loaded with mesoporous silicon nanomaterials according to claim 1, characterized in that: In the preparation of mesoporous silicon nanomaterials, the calcination time is 4h and the calcination temperature is 400℃.
3. The method for preparing the composite hydrogel loaded with mesoporous silicon nanomaterials according to claim 1 or 2, characterized in that: In step 2), the composite hydrogel is prepared according to the following steps: (1) exposing chitosan powder to ultraviolet light overnight for sterilization and dispensing 0.1 g of the chitosan powder in 2.5 ml of deionized water, adding 2.5 ml of a 0.2 M hydrochloric acid solution under stirring to a final concentration of 0.1 M, keeping the solution at room temperature overnight to ensure that the chitosan is completely dissolved, and then storing it at 4°C to obtain a chitosan solution; (2) Dissolve 0.25 g of β-glycerophosphate disodium salt hydrate (β-GP) in 0.5 ml of deionized water and sterilize using a 0.22 μm filter, then add 50 mg of mesoporous silica nanomaterials and shake to mix; (3) The gelling agent synthesized in step (2) is added to the prepared chitosan solution while stirring to obtain a uniformly mixed system, which is then immersed in a 37° C. water bath to prepare a chitosan-based composite hydrogel.
4. A composite hydrogel loaded with mesoporous silicon nanomaterials, characterized in that: According to the method according to any one of claims 1 to 6, the mesoporous silicon nanomaterial is loaded on the thermosensitive hydrogel synthesized with chitosan and sodium β-glycerophosphate as main raw materials, and its hemolysis rate is less than 5%.
5. Use of the composite hydrogel loaded with mesoporous silicon nanomaterials according to claim 4 in a drug-loaded wound dressing.
6. The use according to claim 5, characterized in that: Used in burn dressings.
7. A method for verifying hemolysis of a composite hydrogel loaded with mesoporous silicon nanomaterials according to claim 4, characterized in that: Follow these steps: (1) Collect fresh blood from healthy SD rats, put it into an anticoagulant tube, centrifuge it at 8000r for 5min, discard the supernatant, add it to PBS and centrifuge it again, repeat washing three times, dilute it with PBS, seal it and store it at 4°C to obtain the extracted PBS; (2) Take 5 ml of the composite hydrogel and sterilize it with ultraviolet light overnight, then put it into 50 ml centrifuge tubes, add 45 ml of PBS, seal and soak for 48 hours to obtain diluted blood; (3) Take 500ul of the extracted PBS and diluted blood respectively into a 1.5ml centrifuge tube, incubate in a 37℃ incubator for 2-4h, centrifuge at 8000r for 5min, take the supernatant into a 96-well plate, measure the absorbance at 545nm with an enzyme-labeled instrument, and calculate the hemolysis percentage.
8. The hemolysis verification method of the composite hydrogel loaded with mesoporous silicon nanomaterials according to claim 7, characterized in that: The incubation time of the extract should be 2h.
9. The hemolysis verification method of the composite hydrogel loaded with mesoporous silicon nanomaterials according to claim 7, characterized in that: Hemolysis experiments should use fresh blood from healthy 6-8 week old SD rats.